Strategic Balance between India and Pakistan with respect to “Balance of Power Theory” - Nasim, Jaweriya; Fatima, Khushboo; Noureen, Sajida (Advances in Social Sciences Research Journal, 2020)
India and Pakistan have strained relations since their independence because of serious conflicts like the Kashmir issue and major wars of 1965 and 1971. There is a continuous struggle for dominance among both the states through nuclear weapons and alliances with other nuclear weapons states, which have been addressed in this paper. India had made South Asia nuclear; to which Pakistan develop its nuclear program. Moreover, India and the United States growing relationship have further created an imbalance in the region. In return, Pakistan started strengthening its ties with China to counterbalance the Indian threat. This has been discussed in the paper that both states have actually created balance against one another in the context of the balance of power theory. But it is not going to be long lasting as there is a negative peace among them, and a single event can trigger a major conflict and depict dominance of one over the other.